2014
DOI: 10.1007/s00424-014-1650-8
|View full text |Cite
|
Sign up to set email alerts
|

Salt and gene expression: evidence for [Na+]i/[K+]i-mediated signaling pathways

Abstract: Our review focuses on the recent data showing that gene transcription and translation are under the control of signaling pathways triggered by modulation of the intracellular sodium/potassium ratio ([Na+]i/[K+]i). Side-by-side with sensing of osmolality elevation by tonicity enhancer-binding protein (TonEBP, NFAT5), [Na+]i/[K+]i-mediated excitation-transcription coupling may contribute to the transcriptomic changes evoked by high salt consumption. This novel mechanism includes the sensing of heightened Na+ con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Activation (39). It has been shown also that agonist-induced COX-2 expression is mediated by intracellular Ca 2ϩ (36,58).…”
Section: Ouabain Increases Cox-2 Expression and Activates Pka In Humamentioning
confidence: 99%
See 1 more Smart Citation
“…Activation (39). It has been shown also that agonist-induced COX-2 expression is mediated by intracellular Ca 2ϩ (36,58).…”
Section: Ouabain Increases Cox-2 Expression and Activates Pka In Humamentioning
confidence: 99%
“…3A), the effect that was observed at long-term treatment (24 -48 h) but not at short-term treatment (up to 6 h). Because such cell shape changes may associate with cell death, and because ouabain is known to induce apoptosis of various but not all cell types (38,39), we examined a potential cytotoxic effect of ouabain on HLF by measuring the release of LDH. As shown in Fig.…”
Section: Ouabain Increases Cox-2 Expression and Activates Pka In Humamentioning
confidence: 99%
“…Our previous analyses demonstrated linearly enhanced expression of tubular ENaCs in accordance with genotype and oral salt intake, which is abolished by amiloride treatment. These findings suggest that the amplified intracellular sodium signaling resulted in ENaC gene transcription, which is known as excitation and transcription coupling of monovalent cations [26,27,28,29]. ENaC is considered a major effector of aldosterone-mediated sodium reabsorption and fluid regulation.…”
Section: Discussionmentioning
confidence: 99%
“…86 Up-to-now, there are no reports on mutations of NKCC2 and other renal-specific CCCs in patients with essential hypertension. Schiebl and co-workers found that in mice differential splicing of NKCC2 pre-mRNA is modulated by dietary salt intake, 87 which may be triggered by recently discovered [Na + ] i /[K + ] i -mediated excitation-transcription coupling (for review, see 88 ). Enhanced tubular reabsorption of salt and osmotically-obliged water is important determinant of obesity-related hypertension.…”
Section: Functional Implications Of Nkccsmentioning
confidence: 99%